Adrenal insufficiency resulting from Histoplasmosis infiltration in an immunocompetent patient - Shahar, Mohammad Arif; Ab Wahab, Norasyikin; AbAziz, Aini; Omar , Ahmad Marzuki; Mohd Rusly, Noor Ashikin; Kamaruddin, Nor Azmi (Ministry of Health and Universiti Brunei Darussalem, 2015)
Histoplasmosis usually affects immunocompromised patients. Histoplasmosis infiltration to the adrenal in an immunocompetent host is rare, more so those who presented with adrenal insufficiency. We report a case of 54-year-old previously fit and healthy man who presented with chronic headache of two months duration that was associated with loss of appetite and weight-loss. He had hypotension, hyponatremia, relative hyperkalemia with morning cortisol of 160 nmol/L. Computed tomography of the adrenals showed bilateral enlarged adrenal glands and biopsy confirmed histoplasmosis infiltration. Treatment successfully ameliorate symptoms of hypocortisolism. This case illustrates that immunocompetent patient is still susceptible to adrenal histoplasmosis resulting in adrenal insufficiency.